CoinCalc—A new R package for quantifying simultaneities of event series. (January 2017) - Siegmund, Jonatan F.; Siegmund, Nicole; Donner, Reik V.
Abstract: We present the new R packageCoinCalc for performing event coincidence analysis (ECA), a novel statistical method to quantify the simultaneity of events contained in two series of observations, either as simultaneous or lagged coincidences within a user-specific temporal tolerance window. The package also provides different analytical as well as surrogate-based significance tests (valid under different assumptions about the nature of the observed event series) as well as an intuitive visualization of the identified coincidences. We demonstrate the usage ofCoinCalc based on two typical geoscientific example problems addressing the relationship between meteorological extremes and plant phenology as well as that between soil properties and land cover. Abstract : Highlights: The new R package CoinCalc has been developed. The package gives users the possibility to apply Event Coincidence Analysis. Event Coincidence Analysis is a novel tool to quantify simultaneities in two event time series